Estudio de Mercado para determinar el potencial de negocio en la importación directa por parte de la empresa Let’s Bran - Gamboa-Vargas, Jéssica (Instituto Tecnológico de Costa Rica, 2014)
Before venturing into a new market segment, it’s important to diagnose the reality of the market and the business, without having to incur in bad decisions to develop the market opportunity. Let's Brand is a company dedicated to the direct import of products from anywhere in the world according to consumer needs, by offering the purchasing process or courier service. Let’s Brand works through a service platform of a strategic alliance with high experience in import and logistics, known as Olca Suplidora. Let's Brand requires analyzing the potential market that may have to offer a direct import aimed at SME. For this reason, market research allows collecting information to provide a detailed analysis on the possible development of the project. Market research is aimed at small and medium businesses that currently imported, and companies willing to do so. This study defines the most relevant information of Let's Brand. Also, it describes some concepts for better understanding of the reader, and the methodology used for the research. By collecting and analyzing the results obtained by this market research, it was determined a favorable trend to promote this service in the North Zone. Some recommendations were drafted with the purpose that Let's Brand offers a good quality service and commitment to users, to consider adding value to the service.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2014.
Keywords: Importaciones; Estudio de mercados; Courier; Compras en línea